Estudio de factibilidad para la creación de una empresa recicladora de residuos de aparatos eléctricos y electrónicos (RAEE) en Bogotá (2017)
The main objective of this monograph is to analyze the technical and economic feasibility for the creation of a recycling plant dedicated to the management of waste electrical and electronic equipment (WEEE) at the residential level in the city of Bogotá, according to the need It is observed by households for the correct disposal of these wastes, because in the 21st century, environmental awareness has begun to be generated.